Sighs and Signs of the Spirit : Ghanaian Perspectives on Pentecostalism and Renewal in Africa - Asamoah-Gyadu, J. Kwabena (Johnson Kwabena) (Book collections on Project MUSE., 2015)
This is a scholarly piece of work, presented in a simple, readable style that should make it easily accessible and beneficial to all--scholars and non-scholars alike. In this book, Asamoah-Gyadu returns to many familiar themes; he dialogues with other scholars in the field and also engages with the leaders of Charismatic/Pentecostal Christianity. He consistently allows them to speak for themselves. Though an ordained minister of the Methodist Church, Ghana, Asamoah-Gyadu often points out how the mission-founded churches in Ghana have fallen behind their Charismatic/Pentecostal counterparts and the need for the former to learn from the latter. It is clear that this learning process has already started.